Aspectos clínicos e laboratoriais do carcinoma de suprarrenal na criança: estudo longitudinal no Hospital das Clínicas da UFMG - Nonato Mendonça Lott Monteiro (2016)
Adrenal carcinoma (CSR) is a rare tumor, with heterogeneous clinical behavior and generally bad prognosis. Represents 0.2% of pediatric malignant neoplasms. In Brazil, at South and Southeast regions, this incidence is increased by 10 to 15 times, reaching 4.2/1,000,000 cases. Objectives: Analyze clinical and laboratory characteristics of treated patients at the Hospital das Clínicas da Universidade Federal de Minas Gerais pediatric oncology service with diagnosis of CSR. Patients and methods: Were studied retrospectively the patients with CSR aged up to 17 years and 11 months, admitted in the service in period 2004 to 2015. Results: The series was made up of 13 patients, being 69% smaller than 4 years and 77% female gender. The median age at diagnosis was 2 years. Most of the patients were from the interior of MG. The follow-up time ranged from 4 months to 10 years and 6 months. In 54% of the cases hirsutism has been identified as the initial signal which motivated the first medical consultation, followed by virilization (38.5%). In relation to endocrinology syndromes, virilization was found in 10 female patients who have integrated the material and hypercortisolism demonstrations were identified in all cases. There was a discreet predominance of left adrenal gland involvement (53.8% - 7/13). No patient has presented bilateral tumor. Nine patients were assessed by echocardiography, with normal results. The eight patients who performed chest computed tomography showed results of this exam without changes. Of the eight patients evaluated, 53.8% had advanced bone age in relation to chronological age. The median time between onset of symptoms and the diagnosis was 9.5 months; between the first query and the start of treatment was 6 months. The time between the admission in the oncology service and the diagnosis confirmation was 4 weeks and between admission and treatment was of 1 week, fulfilling the Ministry of Health requirements. Twelve patients had their first consultation held by the pediatrician. Most of the patients were evaluated by a pediatric endocrinologist before the surgical procedure (79.2%). All the tumor resections were performed by a pediatric surgeon. All patients were accompanied by the pediatric oncologist. In relation to laboratory assessment carried out prior to the surgery, 12 patients performed cortisol serum dosage, and 25% of these showed increased values. Dehidroepiandrosterona sulfate was evaluated in 12 patients and was increased in 10 of them. Testosterone was evaluated in 11 patients and showed increased in nine of them. The androstenedione was evaluated in eight and was increased in seven, and the 17-OH-progesterone was measured in nine patients and was increased in eight of them. All patients met the Weiss criteria for the CSR diagnosis. The immunohistochemistry was performed on 61.5% of cases with positivity of the Ki-67 ranging from 0% to 60%; 87.5% had the P53 positive. The tumor weight ranged from 5 to 1040 grams. Most patients (76.9% - 11/13) presented localized disease (stage I 10 patients and II 1 patient) and, of these, 81.8% had less than 4 years of age (9/11). All patients underwent total tumor resection and there was disruption of tumor capsule in only one case. Two patients, with stage III and IV disease (metastasis in liver), received chemotherapy associated to mitotane. Both had over four years. Eleven patients were alive and free of disease at the time of analysis of the results, a patient died as a result of disease progression (stage IV) and there was loss of follow-up of one case. The probability of overall survival for the entire group to 5 years was 92.3 ± 7.4%. Conclusions: Compared to literature, there were no differences regarding clinical and laboratory characterization of the population studied. The favorable evolution of the patients in this series, with literature superior overall survival results, is possibly explained by the low age at diagnosis in the study population, by the predominance of cases with localized disease (stages I and II) and the fact that all patients have undergone complete tumor resection with just a case of ruptured tumor capsule.